Structure Elucidation of an Pentacyclic Triterpenoid and Phenolic from Steam Bark of Vitex Pubescens Vahl - Anwar, Lenny (Talenta Publisher, 2019)
Pentacyclic triterpenoid, betulinic acid (1) and phenolic, p-hydroxybenzoic acid (2), had been isolated for the first time from the stem bark of Vitex pubescens Vahl. The structure of compounds 1 and 2 was determined based on the interpretation of spectroscopic data including UV, IR, NMR (1H-NMR, 13C-NMR, HMQC, HMBC, COSY) and MS, as well as by comparison with those reported data.